The students doth protest too much? Manage campus protests during pandemic. Issue 9 (17th December 2020) - Lyerly, Eric
Abstract : The pandemic has created challenges for campus leadership, ranging from the profound, such as transitions to virtual learning, to the routine, such as increasing access to hand sanitizer. Now that students have returned to campus, pandemic management issues will only grow in complexity, especially if a so‐called second wave swells across the country. If these concerns weren't complicated enough, administrators at many institutions face increased campus protest activity arising from students and employees, chiefly protests related to the Black Lives Matter movement and protests over institutional responses to the pandemic itself, including reopening policies.